2022
DOI: 10.1039/d2qm00449f
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent solvent-free lignin ionic complexes with thermostability toward a luminescent hydrophobic coating material

Abstract: Lignin is one of the abundant natural biomass resources. Developing lignin into fluorescent materials is gaining continuous attractions. In this study, a type of fluorescent lignin ionic complexes (LS-TPEA) is...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…In one of our previous studies on fluorescent-biomolecule-based LCs, we found that the AIE effect of TPEA could be switched on-and-off by changes in the physical state, specifically an ordered structure leading to PL on and disordered structure leading to PL off. 22 Here, we envisioned that by combining a proper amount of TPEA with DNA–DDAB, the PL signal of TPEA might also be changed along with the humidity-induced change in the physical state.…”
mentioning
confidence: 99%
“…In one of our previous studies on fluorescent-biomolecule-based LCs, we found that the AIE effect of TPEA could be switched on-and-off by changes in the physical state, specifically an ordered structure leading to PL on and disordered structure leading to PL off. 22 Here, we envisioned that by combining a proper amount of TPEA with DNA–DDAB, the PL signal of TPEA might also be changed along with the humidity-induced change in the physical state.…”
mentioning
confidence: 99%